A.Y.P.E. Director General Ira Nadeau addressing a crowd from behind a podium, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - Nowell, Frank H., 1864-1950 (1909)
Handwritten on verso: Ira Nadeau. Director General A.Y.P. PH Coll 727.6 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number